A review on micro-electron beam welding with a modernized SEM: Process, applications, trends and future prospect. Issue 2 (November 2019) - Kundu, Anupam; Pratihar, Dilip Kumar; Pal, Abhishek Rudra
Abstract: Electron beam welding (EBW) is a well-established joining method in the field of manufacturing. If this technology is downscaled to a micro-level (i.e., micro-EBW (µ-EBW)), it will be able to solve a variety of problems. The necessity of adopting µ-EBW technology lies with the fact that it can be used from micro-mechanical fabrication to micro-electronics components joining, micro-electro-mechanical system (MEMS), medical instrument, etc. µ-EBW has some special properties like the possibility of obtaining exact focussing of the beam and conducting measurement up to micrometer level, accurate control of energy input, inertia-free manipulation, high-frequency oscillation movement and ability to work under high vacuum chamber. µ-EBW has several important applications like micro-joining and micro-fabrication, which is welding of dissimilar materials. This article deals with a review of the recent developments, significant applications, and advantages of µ-EBW, multiple modes of joining and also some new technologies such as scanning electron microscope, function generator, control software, etc. Finally, the current challenges of this emerging technology and the scopes for future studies have been presented in this article.